Enhancement effect of the aggregate particles on the low-temperature cracking resistance of the asphalt mortar. (5th July 2021) - Du, Jianhuan; Rahman, Ali; Zhou, Zhengfeng; Ai, Changfa; Qiu, Yanjun
Highlights: The enhancement effect of aggregates on the low-temperature cracking resistance of the material Considering the effect of cracks' configuration on the aggregates' enhancement. The RVE of the test specimens was established by the XFEM to study the effect of aggregates on the crack propagation from the perspective of crack tip configuration force. Abstract: On the mesoscale, the aggregate which is a particle-reinforced material, plays an important role in improving the mechanical properties of the pavement material. To study the enhancement effect of the aggregate particles on the low-temperature crack resistance of the asphalt mortar, the asphalt mortar specimens using the aggregate with different particle sizes were formed by applying the static pressure. The indirect tensile test ( IDT ) was carried out to analyze the enhancement effect of the aggregate particles. Also, the pre-cracked asphalt mortar specimens prepared by the waterjet cutting technology were used for IDT . IDT was combined with the extended finite element method (XFEM) to analyze the influence of the initial configuration of the crack on the enhancement effect of the aggregate particles against the low-temperature cracking resistance and the configuration resultant force at the crack tip. It was observed that, under the low-temperature, the aggregate with different particle sizes could suppress the initiation of cracks in the asphalt mortar with different degrees. As a result, an increase in the low-temperature cracking resistance of the asphalt mortar depended on the particle size of the aggregate. The low-temperature cracking resistance of the asphalt mortar significantly decreased with an increase in the initial crack length. The aggregate could suppress such adverse effect of the initial crack length on the low-temperature cracking resistance of the asphalt mortar to a certain extent. On the other hand, as the initial deflection angle of the crack increased, the enhancement effect of the aggregate on the low-temperature cracking resistance of the asphalt mortar gradually weakened. But when the initial deflection angle was larger than 45°, this weakening trend was mitigated due to the 'crack shielding effect' among branch cracks.